The Relationship of Squeeze Strength and Arm Explosion Power to the Ability of Forehand Drive in Tennis Court - M. Sahib Saleh; Nurkadri Nurkadri (Universitas Negeri Medan, 2020)
The abstract This study aims to determine the relationship between the strength of the squeeze of the hand and the explosive power of the arm on the ability of forehand drive in playing tennis. The study population was all students of the Faculty of Sport Science State University of Makassar with a sample of 40 people. The sampling technique used was purposive sampling. Based on data analysis, there was a significant correlation between hand squeeze strength and arm explosive power to the ability of forehand drive in the tennis playing field of the students of the Faculty of Sport Sciences State University of Makassar.